Social Media–Based Secondary Distribution of Human Immunodeficiency Virus/Syphilis Self-testing Among Chinese Men Who Have Sex with Men. (26th June 2020) - Wu, Dan; Zhou, Yi; Yang, Nancy; Huang, Shanzi; He, Xi; Tucker, Joseph; Li, Xiaofeng; Smith, Kumi M; Ritchwood, Tiarney; Jiang, Xiaohui; Liu, Xuan; Wang, Yehua; et al.
Abstract: Background: Social media and secondary distribution (distributing self-testing kits by indexes through their networks) both show strong promise to improve human immunodeficiency virus (HIV) self-testing uptake. We assessed an implementation program in Zhuhai, China, which focused on the secondary distribution of HIV/syphilis self-test kits among men who have sex with men (MSM) via social media. Methods: Men aged ≥16 years, born biologically male, and ever had sex with another man were recruited as indexes. Banner ads on a social media platform invited the participants to apply for up to 5 self-test kits every 3 months. Index men paid a deposit of US$15/kit refundable upon submitting a photograph of a completed test result via an online submission system. They were informed that they could distribute the kits to others (referred to as "alters"). Results: A total of 371 unique index men applied for 1150 kits (mean age, 28.7 [standard deviation, 6.9] years), of which 1141 test results were returned (99%). Among them, 1099 were valid test results; 810 (74%) were from 331 unique index men, and 289 tests (26%) were from 281 unique alters. Compared to index men, a higher proportion of alters were naive HIV testers (40% vs 21%; P < .001). The total HIV self-test reactivity rate was 3%, with alters having a significantly higher rate than indexes (5% vs 2%; P = .008). A total of 21 people (3%) had a reactive syphilis test result. Conclusions: Integrating social media with the secondary distribution of self-test kits may hold promise to increase HIV/syphilis testing coverage and case identification among MSM. Abstract : Compared to index men, significantly more alters who received an human immunodeficiency virus (HIV) self-test from an index case were naive HIV testers and HIV reactive, suggesting the potential for a social media–based secondary distribution strategy in improving HIV testing and case identification.